Pergumulan Politik Hukum Perkawinan Islam Dan Adat Di Indonesia - Kamsi Kamsi (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2012)
The establishment of the law should not be in a vacuum but rather cultural particularities of the community with their cultural roots. Because the law in the service of society, the legal system must also trademark the same cultural roots communities it serves. Therefore, it becomes inevitable that the political vision of making the culture of the community and the interests of different political, economic, social, cultural (poleksosbud) is a parallel society. Accordingly, periodically in line with the historical appearance of terms of customary law, then the exposure will be described in periodically. First is the forms of the Dutch government's policy towards the Islamic law and custom. It is important to understand the different kinds of consequences caused by the policies of the colonial legal system. While the second part of the discussion is the relationship between Islamic law and custom in the independence of Indonesia, so that an image between the two legal systems is obvious.